Status of the PIENU experiment at TRIUMF. (July 2015) - Ito, S; Aguilar-Arevalo, A; Aoki, M; Blecher, M; Britton, D I; Bryman, D A; vom Bruch, D; Chen, S; Comfort, J; Cuen-Rochin, S; Doria, L; Gumplinger, P; et al.
Abstract: The PIENU experiment at TRIUMF aims to measure the branching ratio of pion decays R = Γ(π + → e + ν e + π + → e + νe γ)/Γ(π + →μ + νμ + π + → μ + νμ γ) with precision <0.1%, providing a stringent test of the Standard Model hypothesis of electron-muon universality and a search for new physics.